Linear Momentum 3 With Solution

Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

Collision between two objects

A pendulum is formed of a massless and


inextensible string of length ℓ = 1.8 m ,
having one of its ends C fixed to a support
while the other end carries a particle (P1) of
mass m1 = 200 g. The pendulum is
stretched horizontally. The particle (P1) at
A0 is then launched vertically downward

with a velocity v i of magnitude
vi = 8 m/s. At the lowest position O, a
perfect elastic collision between (P) and
(S2) takes place. The solid (S2) of mass
m2= 800 g is connected to a horizontal spring (R), of negligible mass and of stiffness K, which is
connected on its ends B to a fixed support. Thus (R) moves without friction on a horizontal axis x’Ox
along OB. Just after collision and at the initial instant t0 = 0, the center of (R) coincides with O, the
equilibrium position, and has a velocity of magnitude v’2. At an instant t, the abscissa of (R) is x and the
dx
algebraic value of its velocity is v  . (Doc. 1)
dt
Use g = 10 m/s2, All frictional forces are neglected.
Take: the horizontal plane passing through O as a gravitational potential energy reference.
1- Study of the motion of (P1)
1-1) Calculate the mechanical energy of the system [P1, Earth] at the instant of launching of (P1).
1-2) Prove that the speed v1 of (P1), just before collision at point O, is v1= 10 m/s
2- Elastic collision between (P1) and (S2)
2-1) Name the physical quantities that are conserved during this collision.
2-2) Prove that the velocity vectors of (P1) and (S2) just after collision are respectively:
 
v1,  6 i and v ,2  4 i
 
dP Δ P
2-3) Knowing that the duration of the collision is ∆t = 50 ms and assume that 
dt dt
Determine, using Newton’s 2nd law, the magnitude of the average force exerted by (P1)
over (S2) during collision.
2.4) Deduce the force exerted by S2 over P1.
3- Study of the motion of (S2) after collision
K.E (J)
3-1) Determine the mechanical energy of the system 𝐃𝐨𝐜. 𝟐
𝟔. 𝟒
[(S2) spring, Earth] just after collision at O.
3-2)
3-2-1) Prove that, at any instant t, the expression of the 𝟔
kinetic energy of (S2) is K.E = B- Ax2 𝟒
and deduce the value of B and the expression of A.
3-2-2) The document 2 represents the variation of the 𝟐
kinetic energy of (S2) as function of x2. x2(m2)
𝟎
Determine the value of the maximum compression 𝟎. 𝟎𝟒
xmax of the spring and deduce that the stiffness k of 𝟎. 𝟏𝟑𝟕
the spring is k ≈ 93.4 N/m .
3-3) Determine the position x of (S2) when its kinetic energy is equal to the half of its elastic
potential energy.
4 - In reality the frictional force exists and supposed constant along the path OB
The maximum compression of the spring is 30 cm.
4-1) Calculate the variation in the mechanical energy of the system [(S2), spring, Earth] between
O and position where 𝐱 = 𝐱𝐦𝐚𝐱 .
4-2) Deduce the magnitude of the force of friction.
Part exercise Points
1.1 M.E0 =K.E.+P.E. = ½ m1 V2 + mgl = 10
1.2 M.ED = M.E0 ; ½ m1V2 = 10  V1 = 10 m/s
2.1 Linear momentum is conserved ( sum of external forces is zero)
Kinetic energy of the system is conserved ( elastic collision)
2.2 m2 = 4 m1
      
Pafter  Pbefore  m1v1'  m2 v 2'  m1v 1  m2 v 2'  m1 (v1  v1' )
 
4 v2'  (v1  v1' )......... .....(1)
Elastic collision kinetic energy is conserved K.E.after = K.Ebefore
1 2 1 1
m1 v1'  m 2 v '22  m1 v12  m 2 v '22  m1 (v12  v1'2 )
2 2 2
4 v 2  (v1  v1 )(v1  v1' )......... .....2
'2 '

Divide 2 by 1
 
: v2'  (v1  v1' )......... .....( 3)
  
(1) And (3) gives v1'  -6 i , v'2  10 - 6  4 i
  
2.3 ΔP2  P2  0  3.2 i Kgm/s

   ΔPA
F1/2  W  N 
Δt
  
W  N  0 Action and reactiom
 
F1/2  64 i N.
  
2.4 F2/1  F1/2  64 i N , According to principle of interaction .
3.1 M.E = K.E + P.Eg
1 1
M.E  m 2 v '22   0.8  4 2  6.4 J
2 2
3.2.1 M.E = K.E + P.Ee + P.Eg
1
6.4 = K.E + K x 2
2
K.E = 6.4 – 0.5 K x2
3.2.2 xm is the point where v = 0 (K.E = 0 )
xm2 = 0.137  xm = 0.37 m
0  6,4
 0.5 K  Slope   46.7  K  93.4 N
0.137  0
3.2.3 M.E = K.E + P.Ee + P.Eg
1 3 2 2
M.E  P.E e  P.E e  P.Ee , P.E e  M.E   6.4  4.26 J
2 2 3 3
1 2  4.26
Kx 2  4.26  x 2   0.091  x  0.03 m
2 93.4
4.1 M.E.= M.EF – M,Ei = K.E + P.Ee – 6.4
1
Δ M.E  0   93.4  (0.3)2  2.2 J
2
4.2 M.E.= -f  xm  -2.2 = - 0.3 f
f = 7.33 N

You might also like